(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper we propose a design solution to address the challenges of e-Payment in Kurdistan Regional Government’s public sector. The reality of globalization is upon us due to the advancement in new technologies and telecommunications. The advancement is more apparent in areas such as e-payment that has opened a wide door for service provision regardless of time and location. Kurdistan region is a newly recognized region of Iraq that has made real progress in many areas of governing with some real challenges left to address. Due to the political and economical situation in the country, e-communication infrastructure is not well established and this has caused real problems to many e-services including e-payment. In this paper we investigate the main challenges and obstacles facing e-payment service provision and propose a design solution that will help KRG to overcome some of these challenges. The findings of this paper will contribute towards speeding up the progress that KRG is currently achieving as well as providing alternative strategies for the future.